2012
DOI: 10.1017/s1368980012002698
|View full text |Cite
|
Sign up to set email alerts
|

Overnutrition and associated factors among adults aged 20 years and above in fishing communities in the urban Cape Coast Metropolis, Ghana

Abstract: Objective: The study aimed to highlight the determinants of overnutrition (overweight plus obesity) in fishing communities and establish if these were the same as reported elsewhere in Ghana. Design: Cross-sectional study. Setting: The study was conducted in Idun, Ola and Duakor fishing communities in Cape Coast, Ghana. Subjects: Adults (n 252) aged 20 to 50 years. Results: Results showed that 32 % of participants were overweight/obese (BMI $ 25?0 kg/m 2 ). Participants' mean age was 31?7 (SD 1?0) years, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
(19 reference statements)
3
15
1
Order By: Relevance
“…In the present study, there was a positive association between TF and abdominal obesity. In contrast to our observation, two previous cross-sectional studies from Ghana reported inverse associations between the percentage of energy obtained from total fat and overweight/obesity [16,49]. However, Mogre et al showed a weak inverse association between the absolute quantity of dietary fat intake and both WC and BMI among University students [27].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, there was a positive association between TF and abdominal obesity. In contrast to our observation, two previous cross-sectional studies from Ghana reported inverse associations between the percentage of energy obtained from total fat and overweight/obesity [16,49]. However, Mogre et al showed a weak inverse association between the absolute quantity of dietary fat intake and both WC and BMI among University students [27].…”
Section: Discussioncontrasting
confidence: 99%
“…Although genetic factors play a role in the development of obesity [12,13], the contributions of both total dietary fat [14,15] intake and fat types [12,13] have been suggested. However, the relationship between dietary fats and obesity is debatable [12,[14][15][16][17][18][19][20][21]. Specifically, positive [14,15] and inverse [16] associations have been reported between total fat intake and obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was expected as the lives of young women are likely to become more sedentary when they stop attending school, while eating patterns may shift with more ready access to food. We were expecting marriage to be positively associated with overweight/obesity, as was noted in other studies, but we found that marriage increases BMI only in urban areas and among older girls. In rural areas, marriage was found to increase the risk of being underweight.…”
Section: Discussionsupporting
confidence: 77%
“…Being underweight can be perceived not only as not yet being physically mature but also as not having good health, particularly in contexts where HIV prevalence is high, as is the case in Zambia. Studies reviewing the literature on marital transitions and BMI found that transitions into marriage are associated with higher BMI in the United States, other developed countries, and in Mexico, and that married adults are more likely to be overweight and obese . Finally, in Zambia, breastfeeding is nearly universal during children's first year of life and is common during their second year of life, and has been associated with lower BMI among adult women in other African settings …”
Section: Introductionmentioning
confidence: 99%